A systematic review of treatment options for dermal photosensitivity in erythropoietic protoporphyria - Minder, E I; SchneideR-Yin, X; Steurer, J; Bachmann, L M (Cellular and Molecular Biology, 2015)
Erythropoietic protoporphyria (EPP) is a rare inherited disease characterized by dermal photosensitivity due to the accumulation of photosensitizer protoporphyrin IX. We performed a systematic database search on studies related to treatment of EPP. A total of 25 relevant studies were retrieved, 16 of them dealing with the application of beta-carotene. Two studies were found on each of the three substances, n-acetyl-cysteine (NAC), cysteine, and dihydroxyacetone/Lawson (henna). In addition, single studies on vitamin C, canthaxanthin and UVB treatment respectively, were located. The total number of patients in the 25 studies was 454, including 337 patients in the various beta-carotene trials. Most studies were published in the 1970's. Efficacy criteria were not standardized. Only 5 of the 25 studies were randomized and controlled trials; the rest were either open-label, uncontrolled studies or retrospective case reports. Four of the five well-designed studies suggested lack of efficacy of beta-carotene, NAC and vitamin C. The results of the beta-carotene studies were strongly contradictory and efficacy was inversely correlated with study quality. Our data confirm the opinion of experts in the field who are much more skeptical as to its efficacy than were early proponents of treatment with this agent. We conclude, that the available data are insufficient to prove efficacy of any treatments studied so far in EPP. We emphasize the necessity of high quality efficacy studies in porphyrias and in other rare diseases.